2004
DOI: 10.2298/vsp0404365s
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variability of precuneus in relation to gender and the hemisphere of human brain

Abstract: Precuneus, a quadrangular gyms of the medial surface of the human parietal lobe, is bound by three primary brain sulci and by superior hemispheric border. Precise encephalometric data about precuneus are important in the studies of brain lateralization, sex dimorphism, and brain functions in general. In this study, total and visible (exstrasulcal) surface area of the precuneus were measured on 50 brains of the adult persons (31 male, and 29 female), together with the investigation of its relationship to the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…The predominance of continuous morphological type that we found (95.2%) confirms that primary and secondary areas exhibit less variability than higher order cortical areas [7], but we do not know if the same is true for morphometric differences (variability in areal sizes). We did not find statistically significant differences in the extrasulcal surface area of the PCL between males and females, but morphological and morphometric gender differences have various aspects and are more complex than usually expected [21]. We found two distinct morphological types of the human PCL with a predominance of the continuous type (95.2% of cases), the presence of the lobulo-limbic gyri in 13.1% of cases, and significantly larger PCL extrasulcal surface on the left hemispheres, both in males and females.…”
Section: Discussioncontrasting
confidence: 70%
“…The predominance of continuous morphological type that we found (95.2%) confirms that primary and secondary areas exhibit less variability than higher order cortical areas [7], but we do not know if the same is true for morphometric differences (variability in areal sizes). We did not find statistically significant differences in the extrasulcal surface area of the PCL between males and females, but morphological and morphometric gender differences have various aspects and are more complex than usually expected [21]. We found two distinct morphological types of the human PCL with a predominance of the continuous type (95.2% of cases), the presence of the lobulo-limbic gyri in 13.1% of cases, and significantly larger PCL extrasulcal surface on the left hemispheres, both in males and females.…”
Section: Discussioncontrasting
confidence: 70%
“…A survey 265 on fixed brains suggested that males have larger surface area than females, and that the right 266 side is larger than the left one (Spasojević et al, 2004). A recent MRI analysis evidenced that 267 sexual differences may be due to cortical thickness more than to surface, and that the right 268 side has larger cortical surface but smaller cortical thickness (Bruner et al, 2015a).…”
Section: Sulcal Patterns and Connections 225mentioning
confidence: 99%
“…Metric data on the precuneus based on anatomical (physical) preparations are rare. A survey on fixed brains suggested that males have larger surface area than females, and that the right side is larger than the left one (Spasojević et al, 2004). A recent MRI analysis evidenced that sexual differences may be due to cortical thickness more than to surface, and that the right side has larger cortical surface but smaller cortical thickness .…”
Section: The Extension Of the Precuneal Foldsmentioning
confidence: 99%
“…In general, sulcal patterns are used as a reference for neurosurgical guidance (Ribas et al, 2006). Morphometric evaluations, in this case, may largely depend on the variable nature of the subparietal sulcus (Spasojević et al, 2004). The patterns and connections of this sulcus were addressed recently in two different studies: Gürer et al (2013) analyzed a small sample of 28 post-mortem brains and Kacar et al (2015) studied the MRIs of 200 individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation